Pis'ma Sergeiu Shakhraiu . Pis'ma Sergeiu Shakhraiu . Letters to Sergei Shakhrai . Письма Сергею Шахраю - Radio Free Europe/Radio Liberty Research Institute (RFE/RL Research Institute)
This program was broadcast by Ostankino television (Moscow) in the Russian Federation and recorded by the moniotring group at the Research Institute of Radio Free Europe/Radio Liberty in Munich as part of their effort to track and analyze the official media of the countires of the former Soviet Union. Передача Российской государственной телевизионной и радиовещательной компании (РГТРК) "Останкино" (Москва, Российская Федерация) была записана группой мониторинга Исследовательского Института радиостанции Свободная Европа/Свобода (Мюнхен) как часть проекта по анализу официальных средств информации стран бывшего Советского Союза. Deputy Head of the Government of the Russian Federation, Sergei Shakhrai, answers TV viewers' questions. Featured in the program: Shakhrai, Sergei Mikhailovich (Deputy Prime Minister of the Government of the Russian Federation) Contributors: Karaulov, Andrei (Anchor); Sharapova, Arina (Anchor) Заместитель председателя правительства Российской Федерации Сергей Шахрай отвечает на вопросы телезрителей. В программе участвуют: Шахрай, Сергей Михайлович (Заместитель председателя правительства Российской Федерации) Создатели: Караулов, Андрей (Ведущий/Ведущая); Шарапова, Арина (Ведущий/Ведущая)